Genetic Polymorphism and Expression of CXCR4 in Breast Cancer - Marina Okuyama Kishima; Karen Brajão de Oliveira; Carolina Batista Ariza; Carlos Eduardo Coral de Oliveira; Roberta Losi Guembarovski; Bruna Karina Banin Hirata; Felipe Campos de Almeida; Glauco Akelinghton Freire Vitiello; Kleber Paiva Trugilo; Alda Fiorina Maria Losi Guembarovski; Walter Jorge Sobrinho; Clodoaldo Zago Campos; et al. (Analytical Cellular Pathology)
CXCR4 genetic polymorphisms, as well as their expression level, have been associated with cancer development and prognosis. The present study aimed to investigate the influence of CXCR4 rs2228014 polymorphism on its mRNA and protein expression in breast cancer samples. It was observed that patients presented higher CXCR4 mRNA relative expression (5.7-fold) than normal mammary gland, but this expression was not correlated with patients clinicopathological features (nuclear grade, nodal status, ER status, PR status, p53 staining, Ki67 index, and HER-2 status). Moreover, CXCR4 mRNA relative expression also did not differ regarding the presence or absence of T allele (p=0.301). In the immunohistochemical assay, no difference was observed for CXCR4 cytoplasmic protein staining in relation to different genotypes (p=0.757); however, high cytoplasmic CXCR4 staining was verified in invasive breast carcinoma (p<0.01). All in all, the results from present study indicated that rs2228014 genetic variant does not alter CXCR4 mRNA or protein expression. However, this receptor was more expressed in tumor compared to normal tissue, in both RNA and protein levels, suggesting its promising applicability in the general context of mammary carcinogenesis.